2019
DOI: 10.1177/1098612x19833261
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination with an inactivated canine influenza H3N2 virus vaccine is safe and elicits an immune response in cats

Abstract: Objectives The aim of this study was to evaluate safety and seroconversion when an inactivated H3N2 canine influenza virus (CIV) vaccine was administered to cats. Methods Twenty 7–8-week-old seronegative cats were randomly assigned to two groups of 10 animals each. Cats in treatment group T01 were subcutaneously administered two doses of an adjuvanted placebo 3 weeks apart to serve as non-immunized controls. Cats in treatment group T02 were subcutaneously administered with two doses of H3N2 CIV vaccine at 3 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Recently, it was shown that a commercial inactivated H3N2 canine IAV vaccine was well tolerated and induced seroconversion in cats [ 62 ]. Even if this vaccine was to be licensed for cats, its usage in Europe is not recommended as this virus has been never detected in Europe, and in regions with canine influenza outbreaks infections in cats are very rare.…”
Section: Controlmentioning
confidence: 99%
“…Recently, it was shown that a commercial inactivated H3N2 canine IAV vaccine was well tolerated and induced seroconversion in cats [ 62 ]. Even if this vaccine was to be licensed for cats, its usage in Europe is not recommended as this virus has been never detected in Europe, and in regions with canine influenza outbreaks infections in cats are very rare.…”
Section: Controlmentioning
confidence: 99%
“…Hematological data showed no signi cant differences in the twenty measured hematologic parameters between vaccinated and control groups and indicate the safe pro le of (Antigen alone, SWE Adj, and Alum Adj) in juvenile cats. Overall, all three vaccine formulations showed an acceptable tolerability and safety pro le with outcomes with tolerability in cats reported for an inactivated in uenza virus vaccine [37].…”
Section: Discussionmentioning
confidence: 80%
“…Hematological data showed no significant differences in the 20 measured hematologic parameters between vaccinated and control groups. Overall, all three vaccine formulations showed an acceptable tolerability and safety profile with a similar tolerability to an inactivated influenza virus vaccine in cats ( 34 ).…”
Section: Discussionmentioning
confidence: 97%